Core-shell emulsion, preparation method thereof and curing paint
By using a core-shell emulsion preparation method, combined with functional groups and shell additives, a curing paint with high permeability and high bonding strength was prepared, solving the problems of insufficient permeability and bonding strength in existing technologies and improving the overall performance of the wall.
Patent Information
- Application Number
- CN202511944058.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-02-06
AI Technical Summary
Existing curing paints lack sufficient penetration and bonding strength, making it difficult to effectively address issues such as interface slippage, detachment, stress concentration, and air permeability in walls.
The preparation method of core-shell emulsion involves introducing functional groups such as carboxyl, hydroxyl or epoxy groups into the core layer monomer, combined with shell additives such as chelating agents and silane coupling agents, to form a curing paint with high permeability and high adhesion strength. The lithium silicate aqueous solution crosslinks with lithium ions in the wall to generate an insoluble gel substance to fill the pores.
It improves the penetration and bonding strength of the cured paint, enhances the strength, wear resistance, impermeability and durability of the wall, and has a simple production process and low cost.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials, and particularly relates to a core-shell emulsion, a preparation method thereof and a cured paint. BACKGROUND
[0002] In recent years, with the continuous increase of existing buildings, the problems of wall mortar layer sanding, hollowing, cracking and weathering are increasingly prominent. The traditional surface batch scraping or externally hung steel wire mesh + polymer mortar "covering type" reinforcement idea, although it can cover the defects in the short term, but has the following common disadvantages: 1, poor interface affinity: the reinforcement layer and the base layer are only bonded by mechanical anchoring or thin layer interface agent, which is prone to interface slip and falling under the action of dry-wet and freeze-thaw cycles; 2, stress concentration: the modulus difference between the rigid surface layer and the elastic base layer is large, and the temperature deformation is not coordinated, which leads to secondary cracking; 3, closed air permeability: the water vapor permeation resistance of thick layer organic-inorganic composite coating is high, and the internal moisture vapor of the wall cannot escape in time, which causes salt precipitation, steel corrosion and insulation layer failure; 4, high thickness and high load: the single construction thickness is often ≥5 mm, which causes additional dead load on the old building facade, historical protection wall and prefabricated wall panel, and the process is long, the comprehensive cost is high.
[0003] In view of the above problems, the industry has begun to turn to "penetrating type" reinforcement route, that is, using low viscosity and high activity liquid to impregnate the surface layer of the mortar, penetrating into the base layer by 2-10 mm through capillary action, and generating insoluble crystals or crosslinked network in situ in the pore, so as to restore or improve the compactness, surface hardness and bonding strength of the wall.
[0004] CN113025175A discloses a wet-cured polyurethane penetrating paint for calcium silicate board, which has good sealing effect on light calcium silicate board, can penetrate into the board and form a film at a certain depth below the board surface through wet curing, so that the sealed calcium silicate board has excellent water resistance and moisture resistance. CN114456694A discloses a polyurethane primer and finish paint combination coating, which has high bonding strength and good sealing performance. CN109280480A discloses a high-temperature and high-humidity non-whitening primer, which has the characteristics of no film whitening, no haze, good pore penetration, good leveling and fullness.
[0005] However, the penetration ability and bonding strength of the cured paint in the prior art are still not high enough. Therefore, how to prepare a cured paint with high penetration ability and high bonding strength has become a problem to be solved at present. SUMMARY
[0006] To solve the above technical problems, the purpose of the present application is to provide a core-shell emulsion, a preparation method thereof and a cured paint. The present application prepares a core-shell emulsion, which has high penetration ability, is cured and crosslinked in the wall, and the formed paint film has high bonding strength.
[0007] To achieve the above object, the present application adopts the following technical solutions:
[0008] In the first aspect, the present application provides a core-shell emulsion, the raw materials for preparing the core-shell emulsion include core layer monomers, shell layer monomers, shell layer additives, emulsifiers and initiators; the core layer monomers include functional group-containing monomers and functional group-free monomers A, the functional groups include any one or a combination of at least two of carboxyl, hydroxyl or epoxy; the shell layer monomers include functional group-free monomers B.
[0009] In the present application, an emulsion with a core-shell structure is used. The functional group-containing monomers are included in the core layer monomers. The functional groups can cross-link and polymerize with lithium ions, thereby enhancing the strength of the cured paint on the wall. The functional group-free monomers adjust the minimum film formation temperature of the emulsion, so that the emulsion can better form a film in application.
[0010] Preferably, the functional group-containing monomers include any one or a combination of at least two of methacrylic acid, acrylic acid, hydroxypropyl acrylate, glycidyl methacrylate or acetoacetoxy ethyl methacrylate.
[0011] Among them, methacrylic acid can be abbreviated as MAA, acrylic acid can be abbreviated as AA, hydroxypropyl acrylate can be abbreviated as HPA, glycidyl methacrylate can be abbreviated as GMA, and acetoacetoxy ethyl methacrylate can be abbreviated as AAEM.
[0012] Preferably, the functional group-free monomers A and the functional group-free monomers B each independently include any one or a combination of at least two of butyl acrylate, methyl methacrylate, styrene, acrylamide or 2-ethylhexyl acrylate.
[0013] Among them, butyl acrylate can be abbreviated as BA, methyl methacrylate can be abbreviated as MMA, styrene can be abbreviated as ST, acrylamide can be abbreviated as AM, and 2-ethylhexyl acrylate can be abbreviated as EHA.
[0014] Preferably, the mass percentage content of the methacrylic acid is 1%-17%, for example, it can be 3%, 5%, 8%, 10%, 11%, 12% or 15%, and the like, and further preferably 3%-11%, based on 100% of the mass percentage content of the core layer monomers.
[0015] In the present application, the methacrylic acid (MAA) and Li +The lithium carboxylate is formed, and after drying, the cross-linking is dehydrated, the storage stability is good, and the carboxyl group of MAA can react with the base of the substrate, which is conducive to enhancing the adhesion of the paint film to the substrate. If the amount of MAA is too small, the adhesion and bonding strength of the paint film will be reduced; if the amount of MAA is too large, the storage stability of the paint will decrease, and gelation is prone to occur.
[0016] Preferably, the mass percentage content of the glycidyl methacrylate is 1%-22% based on 100% of the mass percentage content of the core layer monomer, for example, it can be 3%, 3.7%, 5%, 10%, 10.6%, 15% or 20%, and the like, and further preferably 3.7%-10.6%, and the like.
[0017] In the present application, the epoxy group of glycidyl methacrylate (GMA) can undergo ring-opening reaction with the hydroxyl group in lithium silicate, enhancing the interfacial bonding force, and the cross-linking density is high, significantly improving the hardness. If the amount of GMA is too small, it will affect the overall strength of the paint film; if the amount of GMA is too large, it will affect the storage stability of the paint, and gelation is prone to occur during storage.
[0018] Preferably, the mass percentage content of the butyl acrylate is 1%-19% based on 100% of the mass percentage content of the core layer monomer, for example, it can be 4%, 6%, 10%, 14.6% or 18%, and the like, and further preferably 4%-14.6%.
[0019] Preferably, the mass percentage content of the methyl methacrylate is 8%-24% based on 100% of the mass percentage content of the core layer monomer, for example, it can be 9.6%, 12%, 15%, 16.3% or 20%, and the like, and further preferably 9.6%-16.3%.
[0020] Preferably, the mass percentage content of the styrene is 41%-68% based on 100% of the mass percentage content of the core layer monomer, for example, it can be 46%, 50%, 55%, 59% or 65%, and the like, and further preferably 46%-59%.
[0021] Preferably, the mass percentage content of the acrylic acid is 0%-9% based on 100% of the mass percentage content of the core layer monomer, for example, it can be 0.1%, 2%, 4%, 5.7% or 8%, and the like, and further preferably 0-5.7%.
[0022] Preferably, the mass percentage content of the hydroxypropyl acrylate is 2%-23% based on 100% of the mass percentage content of the core layer monomer, for example, it can be 4.8%, 10%, 12.3%, 15% or 20%, and the like, and further preferably 4.8%-12.3%.
[0023] Preferably, based on the mass percentage of the core layer monomer as 100%, the mass percentage of ethyl acetoacetate methacrylate is 0.4%-11%, for example, it can be 1.1%, 3%, 6%, 8% or 10%, and more preferably 1.1%-6%.
[0024] Preferably, based on the mass percentage of the shell monomer being 100%, the mass percentage of the butyl acrylate is 16%-59%, for example, it can be 21%, 25%, 35%, 47% or 55%, and more preferably 21%-47%.
[0025] Preferably, based on the mass percentage of the shell monomer as 100%, the mass percentage of methyl methacrylate is 0%-17%, for example, it can be 0.1%, 2.3%, 8%, 10.2% or 15%, and more preferably 2.3%-10.2%.
[0026] Preferably, based on the mass percentage of the shell monomer as 100%, the mass percentage of styrene is 23%-75%, for example, it can be 25%, 35%, 35%, 55% or 64%, and more preferably 35%-64%.
[0027] Preferably, based on the mass percentage of the shell monomer as 100%, the mass percentage of the acrylamide is 0.1%-6.3%, for example, it can be 0.5%, 1.5%, 3.1%, 4% or 5%, etc., and more preferably 0.5%-3.1%.
[0028] Preferably, based on the mass percentage of the shell monomer as 100%, the mass percentage of the 2-ethylhexyl acrylate is 2.6%-23.1%, for example, it can be 6.3%, 10%, 15%, 18.4% or 20%, and more preferably 6.3%-18.4%.
[0029] Preferably, the mass ratio of the core monomer to the shell monomer is 1:(2-6), for example, it can be 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, etc.
[0030] Preferably, the shell additive includes any one or a combination of at least two of chelating agents, silane coupling agents, or hydrophilic modified nano-SiO2.
[0031] In this invention, the aforementioned substances are added to the shell layer additive to couple lithium ions during storage, stabilizing and curing the paint system; functional groups are introduced into the core layer monomer to crosslink with lithium ions during use. Without the introduction of a shell layer additive to protect the lithium ions, the paint will gel and solidify; if monomers containing functional groups are introduced into the shell layer, they may react with lithium ions during storage, rendering the paint unusable.
[0032] Preferably, the chelating agent accounts for 0.03%-2.8% of the mass of the shell monomer, for example, it can be 0.08%, 0.1%, 0.5%, 1%, 1.5%, 2% or 2.4%, and more preferably 0.08%-2.4%.
[0033] In this invention, compared to silane coupling agents and modified nano-silica stabilizing lithium ions through steric hindrance, the chelating agent exhibits a more efficient and stable chelating effect. The chelating agent coordinates with lithium ions through coordination sites in its molecular structure, resulting in highly efficient stabilization. If the amount of chelating agent is too small, the stored paint will be unstable; if the amount of chelating agent is too large, it will affect lithium ion release, thereby reducing the strength of the dried paint film.
[0034] Preferably, the chelating agent comprises any one or a combination of at least two of ethylenediaminetetraacetic acid, sodium ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetic acid, 4-dodecyl diethylenetriamine, 2-carbamate, and sodium gluconate.
[0035] Preferably, the mass of the silane coupling agent accounts for 0.24%-8.4% of the mass of the shell monomer, for example, it can be 0.63%, 1%, 2%, 2.5%, 3%, 4%, 4.8% or 6%, and more preferably 0.63%-4.8%.
[0036] Preferably, the silane coupling agent includes KH-570 and / or Z-6030.
[0037] Preferably, the mass of the hydrophilic modified nano-SiO2 accounts for 0.53%-6.6% of the mass of the shell monomer, for example, it can be 1%, 1.2%, 1.5%, 2%, 2.5%, 3%, 3.6%, 4% or 5%, and more preferably 1.2%-3.6%.
[0038] Preferably, the D50 particle size of the hydrophilic modified nano-SiO2 is 15-100 nm, for example, it can be 20 nm, 40 nm, 50 nm, 60 nm or 80 nm.
[0039] Preferably, the specific surface area of the hydrophilic modified nano-SiO2 is 100-250 m². 2 / g, for example, could be 120 m 2 / g, 150 m 2 / g、180 m 2 / g、200 m 2 / g or 230 m 2 / g etc.
[0040] Preferably, the silica content of the hydrophilic modified nano-SiO2 is not less than 99.8%.
[0041] Preferably, the emulsifier comprises nonylphenol polyoxyethylene ether ammonium sulfate.
[0042] Preferably, the emulsifier accounts for 0.3%-1.7% of the total mass of the shell monomer and the core monomer, for example, it can be 0.5%, 0.8%, 1%, 1.2% or 1.5%, etc.
[0043] Preferably, the initiator comprises ammonium persulfate.
[0044] Preferably, the initiator accounts for 0.2%-0.8% of the total mass of the shell monomer and the core monomer, for example, it can be 0.3%, 0.4%, 0.5%, 0.6% or 0.7%, etc.
[0045] Preferably, the core-shell emulsion further includes a pH buffer.
[0046] Preferably, the pH buffer accounts for 0.1%-0.5% of the total mass of the shell monomer and the core monomer, for example, it can be 0.2%, 0.25%, 0.3%, 0.35% or 0.4%.
[0047] Preferably, the pH buffer comprises sodium bicarbonate.
[0048] In this invention, a pH adjuster is added to the emulsion to maintain a neutral or slightly alkaline environment during storage. The chelating agent has a strong ability to chelate lithium ions, and the lithium ion concentration is high, so the lithium ions will be chelated by the chelating agent. During the drying process, the wall surface contains a large number of high-valence metal ions, such as calcium ions and magnesium ions, and the pH of the drying process is slightly acidic. The chelating agent preferentially chelates calcium ions and magnesium ions, releasing lithium ions. The released lithium ions will then undergo a coordination reaction with functional groups.
[0049] Preferably, the core-shell emulsion further includes a post-elimination initiator.
[0050] Preferably, the post-elimination initiator comprises tert-butyl hydroperoxide.
[0051] Preferably, the mass of the post-elimination initiator accounts for 0.1%-0.4% of the total mass of the shell monomer and the core monomer, for example, it can be 0.15%, 0.2%, 0.25%, 0.3% or 0.35%.
[0052] Preferably, the core-shell emulsion further includes a post-elimination reducing agent.
[0053] Preferably, the post-elimination reducing agent comprises sodium thiosulfate.
[0054] Preferably, the mass of the post-elimination reducing agent accounts for 0.1%-0.4% of the total mass of the shell monomer and the core monomer, for example, it can be 0.15%, 0.2%, 0.25%, 0.3% or 0.35%.
[0055] In a second aspect, the present invention provides a method for preparing a core-shell emulsion as described in the first aspect, the method comprising the following steps:
[0056] (1) Mix the core layer monomer and part of the emulsifier in water to obtain a core layer pre-emulsion; mix the shell layer monomer, shell layer additive and part of the emulsifier in water to obtain a shell layer pre-emulsion; dissolve the initiator in water to obtain an initiator solution;
[0057] (2) Mix some emulsifier and pH buffer in water, add some core layer pre-emulsion and some initiator solution, and carry out seed polymerization;
[0058] (3) Simultaneously add the remaining core layer preemulsion and part of the initiator solution to polymerize the core layer monomers;
[0059] (4) Add the shell pre-emulsion and the remaining initiator solution dropwise to polymerize the shell monomers and obtain the core-shell emulsion.
[0060] Preferably, the temperature for seed polymerization is 74-80℃, for example, 75℃, 76℃, 77℃, 78℃ or 79℃.
[0061] Preferably, the polymerization time of the core layer monomer is 10-15 min, for example, it can be 11 min, 12 min, 12.5 min, 13 min or 14 min, etc.
[0062] In this invention, the polymerization time of the core layer monomers is taken from the completion of the addition of all core layer pre-emulsions.
[0063] Preferably, the polymerization time of the shell monomer is 0.5-1.5 h, for example, it can be 0.6 h, 0.8 h, 1 h, 1.2 h or 1.4 h.
[0064] Preferably, the polymerization temperature of the shell monomer is 69-72°C, for example, it can be 69.5°C, 70°C, 70.5°C, 71°C or 71.5°C.
[0065] Preferably, the polymerization of the shell monomer further includes a post-processing step. The post-processing method includes adjusting the pH value to 4-5 (e.g., 4.2, 4.4, 4.5, 4.6, or 4.8), adding a post-elimination initiator and a post-elimination reducing agent, and maintaining the temperature for reaction; then cooling to 40-50℃ (e.g., 42℃, 44℃, 45℃, 46℃, or 48℃) and adjusting the pH value to 7-9 (e.g., 7.2, 7.5, 8, 8.5, or 8.8); then cooling to room temperature and filtering.
[0066] Thirdly, the present invention provides a curing paint comprising the following components: a core-shell emulsion as described in the first aspect and an aqueous solution of lithium silicate.
[0067] In this invention, a highly permeable lithium silicate aqueous solution is added to the formula of the curing paint. The lithium ions in the lithium silicate aqueous solution are small and can easily penetrate deep into the wall. They react chemically with free calcium hydroxide to generate an insoluble gel substance, which fills the capillaries and cracks, reduces the porosity of the concrete, and thus improves its strength, wear resistance, impermeability and durability.
[0068] Preferably, the cured paint further includes any one or a combination of at least two of the following: dispersant, film-forming aid, wetting agent, bactericide, defoamer, or preservative.
[0069] Preferably, based on the mass percentage of the cured paint being 100%, the mass percentage of the core-shell emulsion is 17.3%-58%, for example, it can be 20%, 23.8%, 30%, 40%, 47.5% or 50%, and more preferably 23.8%-47.5%;
[0070] Preferably, based on the mass percentage of the cured paint being 100%, the mass percentage of the lithium silicate aqueous solution is 3.2%-24.8%, for example, it can be 6.2%, 10%, 15%, 17.8% or 20%, and more preferably 6.2%-17.8%.
[0071] In this invention, excessive use of lithium silicate aqueous solution will lead to poor storage stability of the cured paint, making it prone to gelation during storage, i.e., spontaneous cross-linking reaction; insufficient use will affect the penetration and curing ability of the cured paint during use, resulting in low strength after film formation.
[0072] Preferably, the lithium silicate aqueous solution contains 20%-25% lithium silicate by mass, for example, 21%, 22%, 22.5%, 23% or 24%.
[0073] Compared with the prior art, the present invention has at least the following beneficial effects:
[0074] (1) The curing paint of the present invention contains lithium silicate. Lithium ions have high permeability and react chemically with free calcium hydroxide in cement hydration products to generate insoluble gel substances, which fill capillary pores and cracks, reduce concrete porosity, and thus improve its strength, wear resistance, impermeability and durability. Silicic acid reacts chemically with free calcium hydroxide to generate insoluble calcium silicate gel. The two complement each other and improve the strength of the inner wall surface layer.
[0075] (2) The emulsion synthesized in this invention has functional monomers such as carboxylic acid groups, epoxy groups, and hydroxyl groups. During the drying process, after the chelating agent releases lithium ions, these functional monomers can coordinate with lithium ions and undergo cross-linking reactions to enhance the strength of the dry film. At the same time, the lithium silicate aqueous solution is stabilized by chelating agents, amide groups, silane coupling agents, and other substances, thereby improving the storage stability of the system.
[0076] (3) The production process of the emulsion of the present invention is simple and the production cost is low, making it suitable for large-scale promotion and application. Detailed Implementation
[0077] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be considered as specific limitations of the invention. Unless otherwise specified, the processes used in the embodiments of the present invention are conventional processes in the art.
[0078] The sources of some of the raw materials used in the preparation of this invention are as follows:
[0079] Disodium EDTA: Shandong Bokai Chemical Technology Co., Ltd., disodium ethylenediaminetetraacetate;
[0080] Silane coupling agent KH-570: Guangzhou Jianshuang Chemical Technology Co., Ltd., KH-570;
[0081] Hydrophilic modified nano-SiO2: Hubei Huifu Nanomaterials Co., Ltd., hydrophilic HL-260;
[0082] Lithium silicate aqueous solution: Shandong Xinyida Chemical Technology Co., Ltd., lithium silicate content by mass is 23.8%;
[0083] Dispersant: Sanopco Co., Ltd., SN-5040;
[0084] Film-forming aid: Eastman, TEXANOL ester dodecyl;
[0085] Wetting agent: Wacker Chemie, BYK-154;
[0086] Bactericide: Wanhua Tianhe New Material Technology Co., Ltd., Kathon preservative;
[0087] Defoamer: Wacker Chemie, BYK-141;
[0088] Preservative: Shandong Kason New Materials Co., Ltd., isothiazolinone 14;
[0089] The emulsifier, nonylphenol polyoxyethylene ether ammonium sulfate, was purchased from Solverodia and its brand name was RHODAPEXCO-436.
[0090] Example 1
[0091] This embodiment provides a core-shell emulsion. The raw materials for preparing the core-shell emulsion are shown in Tables 1 and 2. The amounts of the raw materials in Tables 1 and 2 are all by weight.
[0092] The preparation method of the core-shell emulsion includes the following steps:
[0093] (1) Disperse the core layer monomer and 0.5 parts of emulsifier evenly with water to obtain a core layer pre-emulsion;
[0094] (2) Disperse the shell monomer, shell additive and 1.2 parts of emulsifier evenly with water to obtain a shell pre-emulsion;
[0095] (3) Disperse the initiator and water evenly to obtain an initiator solution;
[0096] (4) Add water to 0.5 parts of emulsifier, add pH buffer and disperse evenly, heat to 80°C, add 2% core layer pre-emulsion and 0.1% initiator solution, and carry out seed polymerization;
[0097] (5) Simultaneously add 98% of the core layer preemulsion and 24.9% of the initiator solution to polymerize the core layer monomer. After the core layer monomer is added, keep warm for 10 min.
[0098] (6) Add shell pre-emulsion and 75% initiator solution to polymerize shell monomers. After adding shell pre-emulsion, cool down to 70°C, keep warm for 1 hour, adjust pH to 4-5, add post-elimination initiator and post-elimination reducing agent, keep warm to eliminate residual monomers.
[0099] (7) Cool down to 45°C and adjust the pH value to 7-9, then cool down to room temperature, filter, and obtain the core-shell emulsion.
[0100] The emulsifier is nonylphenol polyoxyethylene ether ammonium sulfate, with an amount of 2.2 parts; the initiator is ammonium persulfate, with an amount of 0.75 parts; the pH buffer is sodium bicarbonate, with an amount of 0.45 parts; the post-elimination initiator is tert-butyl hydroperoxide, with an amount of 0.375 parts; and the post-elimination reducing agent is sodium thiosulfate, with an amount of 0.375 parts.
[0101] Examples 2-9
[0102] Examples 2-9 each provide a core-shell emulsion, differing from Example 1 only in the different raw materials used in preparation as shown in Tables 1 and 2.
[0103] Table 1
[0104]
[0105] Table 2
[0106]
[0107] Application Example 1
[0108] This application example provides a curing paint, the components of which are shown in Table 3, which represents the mass percentage of each component in the curing paint.
[0109] The method for preparing the cured paint includes the following steps:
[0110] First, add pure water to the dispersion tank and stir at 500 rpm. Then, weigh out the emulsion, lithium silicate aqueous solution, dispersant, film-forming aid, and wetting agent in sequence and stir thoroughly for 10 minutes. Next, weigh out the bactericide, defoamer, and preservative and stir thoroughly for 5 minutes. Pour out the dispersion and rinse the dispersion tank with pure water. Add the rinsing solution to the dispersion and stir evenly to obtain the cured paint.
[0111] Application Example 2-12
[0112] Application Examples 2-12 each provide a curing paint, differing from Application Example 1 only in the components listed in Table 3. In Table 3, pure water A is the pure water added to the dispersion tank for the first time, and pure water B is the pure water used for the final rinsing of the dispersion tank.
[0113] Table 3
[0114]
[0115] Test method:
[0116] Storage stability: Pour 0.5L of cured paint into a suitable container, leaving approximately 10% space inside. Seal the container and place it in a constant temperature drying oven at (50±2)℃. Remove the container after 14 days and place it at (23±2)℃ for 3 hours. Open the container and stir with a spatula or stirring rod. It is permissible for some sediment to be present at the bottom of the container. If the sediment is easily mixed evenly after stirring and there are no hard lumps, it is rated as "passed"; otherwise, it is rated as "failed".
[0117] Low-temperature storage stability: Three cycles of testing were conducted according to Method A in GB / T 9268-2008;
[0118] Untreated bond strength (14 days): Tested according to JC / T 907-2018;
[0119] Water immersion bond strength: Tested according to JC / T 907-2018;
[0120] Adhesion strength of interior wall putty after applying 0.3 g of paint film: Refer to JGT 298-2010 Test for Interior Building Putty;
[0121] Paint film adhesion: Tested according to GB / T 9286-1998;
[0122] Permeability: Refer to Appendix A of JG / T 210-2018 for testing. A permeability value of 0-0.5 mL indicates that the permeability is qualified.
[0123] The test results are shown in Table 4.
[0124] Table 4
[0125]
[0126] The test results show that:
[0127] (1) As can be seen from Application Examples 1-12, the present invention prepares a core-shell emulsion and uses it in a curing paint, and the resulting paint film has high bonding strength.
[0128] (2) By comparing Application Example 2 with Application Examples 5-8, it can be seen that the present invention improves the storage stability, bonding strength and adhesion of the cured paint by further limiting the amount of specific monomers.
[0129] A comparison of Application Example 2 with Application Examples 9-10 shows that the present invention further introduces a specific amount of chelating agent into the core layer to protect lithium ions during storage and further improve the performance of the cured paint.
[0130] By comparing Application Example 2 with Application Examples 11-12, it can be seen that the present invention further adds a specific amount of lithium silicate aqueous solution to the cured paint to improve the strength, wear resistance, impermeability and durability of the cured paint.
[0131] In summary, this invention improves the performance of the cured paint by adding a core-shell emulsion. The untreated adhesion strength is 1.22-1.53 MPa, the water-immersion treated adhesion strength is 1.17-1.41 MPa, the adhesion strength after brushing 0.3 g of paint film onto interior wall putty is 0.63-0.89 MPa, the paint film adhesion is Grade 1, the water permeability is 0.16-0.34 mL, and both storage stability and low-temperature storage stability are satisfactory.
[0132] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A core-shell emulsion, characterized in that, The raw materials for preparing the core-shell emulsion include core monomers, shell monomers, shell additives, emulsifiers, and initiators; The core layer monomer includes a monomer containing a functional group and a monomer A without a functional group, wherein the functional group includes any one or a combination of at least two of carboxyl, hydroxyl or epoxy groups; The shell monomer includes monomer B, which does not contain functional groups.
2. The core-shell emulsion according to claim 1, characterized in that, The monomer containing the functional group includes any one or a combination of at least two of methacrylic acid, acrylic acid, hydroxypropyl acrylate, glycidyl methacrylate or ethyl acetoacetate; Preferably, monomer A, which does not contain functional groups, and monomer B, which does not contain functional groups, each independently comprises any one or a combination of at least two of butyl acrylate, methyl methacrylate, styrene, acrylamide, or 2-ethylhexyl acrylate. Preferably, based on the mass percentage of the core layer monomer being 100%, the mass percentage of the methacrylic acid is 1%-17%; Preferably, based on the mass percentage of the core layer monomer being 100%, the mass percentage of the glycidyl methacrylate is 1%-22%; Preferably, the mass ratio of the core monomer to the shell monomer is 1:(2-6).
3. The core-shell emulsion according to claim 1 or 2, characterized in that, The shell additive includes any one or a combination of at least two of chelating agents, silane coupling agents, or hydrophilic modified nano-SiO2. Preferably, the chelating agent accounts for 0.03%-2.8% of the mass of the shell monomer; Preferably, the chelating agent comprises any one or a combination of at least two of the following: ethylenediaminetetraacetic acid, sodium ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetic acid, 4-dodecyl diethylenetriamine, 2-carbamate, and sodium gluconate. Preferably, the mass of the silane coupling agent accounts for 0.24%-8.4% of the mass of the shell monomer; Preferably, the silane coupling agent includes KH-570 and / or Z-6030; Preferably, the hydrophilic modified nano-SiO2 accounts for 0.53%-6.6% of the mass of the shell monomer; Preferably, the D50 particle size of the hydrophilic modified nano-SiO2 is 15-100 nm; Preferably, the specific surface area of the hydrophilic modified nano-SiO2 is 100-250 m². 2 / g.
4. The core-shell emulsion according to any one of claims 1-3, characterized in that, The emulsifier includes nonylphenol polyoxyethylene ether ammonium sulfate; Preferably, the emulsifier accounts for 0.3%-1.7% of the total mass of the shell monomer and the core monomer; Preferably, the initiator comprises ammonium persulfate; Preferably, the initiator accounts for 0.2%-0.8% of the total mass of the shell monomer and the core monomer; Preferably, the core-shell emulsion further includes a pH buffer; Preferably, the pH buffer accounts for 0.1%-0.5% of the total mass of the shell monomer and the core monomer; Preferably, the pH buffer comprises sodium bicarbonate; Preferably, the core-shell emulsion further includes a post-elimination initiator; Preferably, the post-elimination initiator comprises tert-butyl hydroperoxide; Preferably, the mass of the post-elimination initiator accounts for 0.1%-0.4% of the total mass of the shell monomer and the core monomer; Preferably, the core-shell emulsion further includes a post-elimination reducing agent; Preferably, the post-elimination reducing agent comprises sodium thiosulfate; Preferably, the mass of the post-elimination reducing agent accounts for 0.1%-0.4% of the total mass of the shell monomer and the core monomer.
5. A method for preparing a core-shell emulsion as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: (1) Mix the core layer monomer and part of the emulsifier in water to obtain a core layer pre-emulsion; mix the shell layer monomer, shell layer additive and part of the emulsifier in water to obtain a shell layer pre-emulsion; dissolve the initiator in water to obtain an initiator solution; (2) Mix some emulsifier and pH buffer in water, add some core layer pre-emulsion and some initiator solution, and carry out seed polymerization; (3) Simultaneously add the remaining core layer preemulsion and part of the initiator solution to polymerize the core layer monomers; (4) Add the shell pre-emulsion and the remaining initiator solution dropwise to polymerize the shell monomers and obtain the core-shell emulsion.
6. The preparation method according to claim 5, characterized in that, The temperature for seed polymerization is 74-80℃; Preferably, the polymerization time of the core layer monomer is 10-15 min; Preferably, the polymerization time of the shell monomer is 0.5-1.5 h; Preferably, the polymerization temperature of the shell monomer is 69-72°C.
7. The preparation method according to claim 5 or 6, characterized in that, The polymerization of the shell monomers also includes a post-processing step. The post-processing method includes adjusting the pH value to 4-5, adding a post-elimination initiator and a post-elimination reducing agent, and maintaining the reaction temperature; then cooling to 40-50℃ and adjusting the pH value to 7-9; then cooling to room temperature and filtering.
8. A curing paint, characterized in that, The cured paint comprises the following components: The core-shell emulsion and the aqueous lithium silicate solution as described in any one of claims 1-4.
9. The curing paint according to claim 8, characterized in that, The cured paint also includes any one or a combination of at least two of the following: dispersant, film-forming aid, wetting agent, bactericide, defoamer, or preservative.
10. The curing paint according to claim 8 or 9, characterized in that, Based on the curing paint having a mass percentage of 100%, the core-shell emulsion has a mass percentage of 17.3%-58%, more preferably 23.8%-47.5%; Preferably, based on the mass percentage of the cured paint being 100%, the mass percentage of the lithium silicate aqueous solution is 3.2%-24.8%, more preferably 6.2%-17.8%.
Citation Information
Patent Citations
Varnish primer without whitening at high temperature and high humidity and preparation method thereof
CN109280480A
Moisture-curing polyurethane permeable paint for calcium silicate board and application of permeable paint
CN113025175A
Polyurethane primer and finishing coat combined coating
CN114456694A